KIA-CHAT: A QnA Chatbot for Postnatal and Newborn Care - Vinarti, Retno Aulia; Sani, Nisfu Asrul; Amalia, Rizki; Sulistiyani, Endang; Adistha Eka Noveyani; Edward Suryaputra; Muhammad Azhar Arwan (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Postnatal care information is relatively less provided than information about prenatal or pregnancy. Several causes of this is the mothers already delivered the baby safely, and soon after the baby's birth, mothers will be busy taking care of the newborns. They frequently miss their postnatal meeting with doctors because of these reasons. Aims: Therefore, this article aims to develop a chatbot in which the knowledge is taken from Buku KIA and focus group discussion. Method: The targeted users of the KIA chatbot are postpartum mothers with live newborns. Rapid Application Development method is used to develop the KIA chatbot. The KIA chatbot is constructed using Google Dialog Flow with Telegram-based messenger. Results: The chatbot evaluation follows the Chatbot Usability Questionnaire with an overall score is 84.23 out of 100. Sixty-nine respondents confess that the KIA chatbot is easy to use and the knowledge is easy to comprehend. But, since the chatbot provides the answer options, the users feel some limitations. One of the limitations is they are unable to type their questions to the chatbot; only type the numerical order of the answer options. Conclusion: However, this limitation also brings another advantage to the mothers who have no time to type because of busy taking care of the newborns.